Primary school teachers' attitudes about children with attention deficit/hyperactivity disorder and the role of pharmacological treatment. (April 2014) - Moldavsky, Maria; Pass, Sarah; Sayal, Kapil
Background: Clinical experience and research suggest that teachers' attitudes about attention deficit/hyperactivity disorder (ADHD) are an important factor influencing access to specialist assessment and treatment, including medication. Methods: We performed a thematic analysis of comments written by primary school teachers who participated in a case-vignette study investigating the ability of teachers to recognise ADHD. Teachers read one of four types of vignette describing the behaviour of a nine-year-old child who met diagnostic criteria for ADHD (either a boy or a girl with inattentive or combined subtype of ADHD). They answered questions (identical for all types of vignette) about their views regarding the problems and their management. Teachers were invited to add their own comments. Results: Altogether 496 teachers from 110 schools completed the questionnaire: 250 (50%) teachers from 94 schools wrote at least one comment, adding up to 341 comments. Regarding their views on the need to refer the child to specialist services, 32 teachers made comments that reflected caution. The most frequent comments were that it was too early to say whether a referral was necessary, the problems were not severe enough or the main support would come from school. Teachers also reported a lack of knowledge about specialist services or criticised them. When asked whether medication might be beneficial for the child, 125 teachers expressed hesitant or negative views: that it was premature to express an opinion about medication or too soon to give medication to the child; that medication was not necessary or should not be used at all; or that the problems were not severe enough or were emotional in nature. Only five teachers reported having a positive experience of the effect of medication. Conclusion: Teachers' comments suggested a strong preference in using within-school strategies for the management of children with ADHD. Teachers were reluctant to endorse medication for DHD and expressed negative views about its use. Health services should support teachers' management of ADHD-related behaviours in school and provide information to increase teachers' ability to identify the need for a referral to specialist health services.